The dynamics of Chlorella spp. abundance and its relationship with water quality parameters in intensive shrimp ponds - HAYATI SOEPRAPTO; HERI ARIADI; UBAD BADRUDIN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Soeprapto H, Ariadi H, Badrudin U. 2023. The dynamics of Chlorella spp. abundance and its relationship with water quality parameters in intensive shrimp ponds. Biodiversitas 24: 2919-2926. Chlorella spp. is a plankton genus belonging to the phylum Chlorophyta and is commonly found in the shrimp farming ponds. This plankton might serve as natural feed especially for the post-larvae stage shrimps. This study aims to investigate the dynamics of Chlorella spp. abundance and its correlation with the N:P ratio in the intensively managed shrimp ponds. The study was conducted using a causal ex-post facto design with data collection through purposive sampling. The results showed that the plankton abundance in the observed ponds was moderate consisted of 4 class and 7 genera. The dominant genus was Chroococcus spp. and Chlorella spp. with abundance ranging from 2.50E+05 to 2.60E+05 cells/mL. Plankton abundance correlated with water quality conditions, including pH of 7.9, salinity of 19-20‰, temperature of 28.50-28.75°C, dissolved oxygen of 5.12-5.39 mg/L, nitrite of 0.035-0.072 mg/L, phosphate of 0.011-0.025 mg/L, organic matter of 95.77-102.32 mg/L, and alkalinity of 125-130 mg/L. There was also correlation between the increase in plankton biomass and nutrient solubility. The abundance of Chlorella spp. was negatively correlated with the N:P ratio of the water in the ponds. Based on dynamic model analysis, the most ideal N:P ratio is 1:20 from several simulations of 1:10, 1:20, 1:30, and 1:40. The dynamics of Chlorella spp. abundance followed an oscillatory pattern from the beginning of cultivation to harvest with the most ideal N:P ratio of 1:20. This understanding is important for making environmental engineering concepts in pond aquatic ecosystems.